Metal activated carbon as an efficient filler for high‐density polyethylene nanocomposites. Issue 8 (24th April 2020) - Nisar, Muhammad; Thue, Pascal S.; Maghous, Myriam B.; Geshev, Julian; Lima, Eder C.; Einloft, Sandra
Abstract: interesting properties of magnetic nanocomposites have attracted attention of both academic and industrial researchers. In this work, thermal, mechanical, morphological, and magnetic properties of polyethylene (PE) nanocomposites were inspected using carbon‐based magnetic fillers (CNi, CCo, and CFe). The melt mixing method was employed to prepare the nanocomposites using small amounts of filler ranging up to 2 wt%. Wood sawdust pyrolysis produces carbonized material activated by Ni, Co, or Fe salts and used as filler. The structural analysis was carried out using Fourier transform infrared spectroscopy indicating that the polymer chemical structure remains unaltered with the filler addition. Thermal stability of nanocomposites as well as the determination of metal amount in the carbon‐based fillers was investigated by thermogravimetric analysis. Filler introduction enhanced the onset and the maximum degradation temperatures up to 11°C and 8°C, respectively. The crystallization and melting temperatures examined by differential scanning calorimetry remained unchanged as compared to neat PE whereas the percent crystallinity was improved up to 8%. The incorporation of the filler leads to the improvement in the elastic modulus of the polymer matrix. The addition of 2.0 wt% of the metal‐carbonized filler in the diamagnetic polymer resulted in a thermoplastic nanocomposite with ferromagnetic behavior. Abstract : High‐density polyethylene nanocomposites were obtained by melt mixing method using up to 2% of carbon‐based magnetic fillers (CNi, CCo, and C‐Fe). Thermal, mechanical, morphological, and magnetic properties were evaluated. The addition of 2.0 wt% of the metal‐carbonized filler in the diamagnetic polymer resulted in a thermoplastic nanocomposite with ferromagnetic behavior.